Characterization of insulated-gate bipolar transistor temperature on insulating, heat-spreading polycrystalline diamond substrate. (5th December 2016) - Umezawa, Hitoshi; Shikata, Shin-ichi; Kato, Yukako; Mokuno, Yoshiaki; Seki, Akinori; Suzuki, Hiroshi; Bessho, Takeshi
Abstract: Polycrystalline diamond films have been utilized as direct bonding aluminum (DBA) substrates to improve cooling efficiency. A diamond film with a high quality factor was characterized by Raman spectroscopy and showed a high thermal conductivity of more than 1800 W m −1 K −1 and a low leakage current, even at an applied bias of 3 kV, because of the suppression of electrical conduction through the grain boundaries. The operating temperatures of Insulated-gate bipolar transistors (IGBTs) on diamond DBAs were 20–28% lower than those on AlN DBAs. The thermal resistivity of the diamond DBA module was 0.32 °C/W. The uniformity of the temperature distribution on a diamond DBA was excellent.